Comparing the Effectiveness of the Incredible Years Program and the Hanen Parent Training Program on Internalized Stigma Among Mothers of Children with Autism Spectrum Disorder - Bashiri, Niloufar Sadat; Emadian, Seyyedeh Olia; Salim Bahrami, Seyyedeh Hamideh (Iranian Journal of Neurodevelopmental Disorders, 2027)
Purpose: The present study aimed to compare the effectiveness of the Incredible Years Program and the Hanen Parent Training Program in reducing internalized stigma among mothers of children with autism spectrum disorder (ASD).Methods and Materials: This quasi-experimental study employed a pretest–posttest design with a control group and follow-up assessment. The statistical population consisted of all mothers of children diagnosed with ASD who attended an autism center in Gorgan, Iran. Using G*Power software, the required sample size was estimated based on a statistical power of 0.80, an effect size of 0.50, and a significance level of 0.05. Accordingly, 45 eligible mothers were selected through purposive sampling and assigned non-randomly to three groups of 15 participants: the Incredible Years intervention group, the Hanen Parent Training intervention group, and the control group. Internalized stigma was assessed using the Internalized Stigma Questionnaire developed by Ritsher et al. Data collected across the pretest, posttest, and follow-up stages were analyzed using SPSS version 24. A two-way repeated-measures analysis of variance was employed to examine changes over time, between-group differences, and the interaction between time and intervention condition.Findings: The inferential analyses indicated a statistically significant effect of time and a significant time-by-group interaction on internalized stigma (p < 0.05), demonstrating that changes in stigma differed significantly across the three study groups. Both the Incredible Years Program and the Hanen Parent Training Program produced significant reductions in internalized stigma from pretest to posttest, and these improvements were maintained at follow-up. Comparative analyses further indicated significant differences between the intervention groups and the control group, confirming the effectiveness of both parent-focused interventions in reducing internalized stigma among mothers of children with ASD.Conclusion: The findings suggest that both the Incredible Years Program and the Hanen Parent Training Program can effectively reduce internalized stigma among mothers of children with ASD. By strengthening parenting competencies, enhancing understanding of the child’s developmental characteristics, and improving parents’ coping and interactional skills, these interventions may help mothers develop more adaptive perceptions of themselves and their parenting experiences. Accordingly, these structured parent-training programs may be incorporated into psychological and family-centered services provided to families of children with ASD.